Epidemiological and Clinical Insights into the Enterovirus D68 Upsurge in Europe 2021-2022 and Emergence of Novel B3-Derived Lineages, ENPEN Multicentre Study - Simoes, Margarida Pires; Hodcroft, Emma B; Simmonds, Peter; Albert, Jan; Alidjinou, Enagnon K; Ambert-Balay, Katia; Andrés, Cristina; Antón, Andrés; Auvray, Christelle; Bailly, Jean-Luc; Baldanti, Fausto; Bastings, Capser; et al. (The Journal of infectious diseases, 2024)
Enterovirus D68 (EV-D68) infections are associated with severe respiratory disease and acute flaccid myelitis (AFM). The European Non-Polio Enterovirus Network (ENPEN) aimed to investigate the epidemiological and genetic characteristics of EV-D68 infections and its clinical impact during the fall-winter season of 2021-2022. From 19 European countries, 58 institutes reported 10 481 (6.8%) EV-positive samples of which 1004 (9.6%) were identified as EV-D68 (including 852 respiratory samples). Clinical data were reported for 969 cases; 78.9% of infections were reported in children (0-5 years); and 37.9% of cases were hospitalized. Acute respiratory distress was commonly noted (93.1%) followed by fever (49.4%). Neurological problems were observed in 6.4% of cases including 6 diagnosed with AFM. Phylodynamic/Nextstrain and phylogenetic analyses based on 694 sequences showed the emergence of 2 novel B3-derived lineages, with no regional clustering. In conclusion, we describe a large-scale European EV-D68 upsurge with severe clinical impact and the emergence of B3-derived lineages.
Keywords: infekce dýchací soustavy; acute flaccid myelitis (AFM); dospělí; enterovirové infekce; Europe; Female; Infant; European Non-Polio Enterovirus Network (ENPEN); předškolní dítě; dítě; enterovirus D68 (EV-D68); novorozenec; Adult; nonpolio enterovirus (NPEV); mladý dospělý; ženské pohlaví; Adolescent; Neuromuscular Diseases; neuromuskulární nemoci; lidé; Infant, Newborn; Evropa; lidský enterovirus D; Central Nervous System Viral Diseases; Respiratory Tract Infections; Phylogeny; Middle Aged; Myelitis; myelitida; Male; kojenec; Aged; Child, Preschool; Young Adult; Enterovirus D, Human; lidé středního věku; Child; respiratory infection; senioři; mužské pohlaví; fylogeneze; Enterovirus Infections; mladiství; virové nemoci CNS; Humans